Symmetric and Nonsymmetric Flame Spread between Parallel Plates of Thick Combustible Solid - Matsuoka, Tsuneyoshi; Murakami, Satoshi; Yamazaki, Takuya; Nakamura, Yuji (Combustion science and technology, 2021)
To identify the occurrence conditions of a symmetry-breaking phenomenon, numerical simulations of flame spread along parallel, combustible plates are performed. Two-dimensional, time-dependent conservation equations for gas-phase with a one-step global reaction coupled to one-dimensional heat conduction for the solid-phase are simultaneously solved. The flame spread having two leading edges was successfully simulated and the behaviors were examined under various flow velocities and channel heights. Based on the time histories of the leading edges, the simulated flame behaviors are distinguished into three modes: symmetric, asymmetric and oscillation, in addition to the extinction. The occurrence conditions of those modes are summarized. The results indicate that the local extinction caused by an excess of the scalar dissipation rate is a key process of the symmetry-breaking. Since coexistence of flames in narrow channel is unstable, the local extinction occurs to achieve a stable state for the system to burn.